Preferred sources of help for mental health problems among Chilean adolescents: a descriptive study - Cecilia Olivari; Carlos Mellado; Rocío Casañas; Nancy Espinosa-Díaz; Jaime Fuster-Villaseca (Permanyer, 2021)
Background: A timely search for professional help regarding mental health issues in adolescents is critical in preventing severe disorders. However, adolescents generally tend not to seek help. This investigation aimed to study Chilean adolescents' willingness to seek help in mental health issues by identifying their preferred help-seeking sources. Methods: We conducted a cross-sectional-correlational study with 493 high school students between 14 and 19 years of age (mean ± standard deviation = 16.28 ± 1.29). The instruments we used were the general help-seeking questionnaire (vignette version), adapted and validated in Chile, and a sociodemographic questionnaire. Results: Data showed that adolescents are more willing to seek help from informal rather than from formal sources. We identified no sex differences in terms of willingness to seek help from formal sources. However, males were more willing to seek help from informal sources. Conclusions: Similar to other cultures, Chilean adolescents are more willing to seek help from informal sources regarding mental health problems.